2010
DOI: 10.1158/1055-9965.epi-10-0064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mRNA and Protein Measures of Cytokines following Vaccination with Human Papillomavirus-16 L1 Virus-like Particles

Abstract: Background: mRNA expression signatures are frequently used as surrogate measures of cellular function and pathway changes. Few studies have directly compared results obtained using gene expression and multiplex protein assays for corresponding gene products.Methods: We used data available from a clinical trial of a human papillomavirus-16 vaccine that tracked gene expression and cytokine/chemokine production by peripheral blood mononuclear cells stimulated in culture with various antigens to evaluate the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 24 publications
8
85
0
Order By: Relevance
“…Inhibition of protein synthesis/translational efficiency during salinity stress would also explain the much higher levels of mRNA induction at 34 and 90 ppt compared with the magnitude of the corresponding protein increase. Stronger increases in mRNA compared with corresponding protein abundances in response to stress are not uncommon and have been observed for many other systems (Kaufmann and van Oudenaarden, 2007;Persson et al, 2009;Shebl et al, 2010;Schwanhäusser et al, 2011). Interestingly, two different MIPS mRNA variants are present in tilapia gill epithelium.…”
Section: Mips/impa Mrna Versus Protein Regulationmentioning
confidence: 80%
“…Inhibition of protein synthesis/translational efficiency during salinity stress would also explain the much higher levels of mRNA induction at 34 and 90 ppt compared with the magnitude of the corresponding protein increase. Stronger increases in mRNA compared with corresponding protein abundances in response to stress are not uncommon and have been observed for many other systems (Kaufmann and van Oudenaarden, 2007;Persson et al, 2009;Shebl et al, 2010;Schwanhäusser et al, 2011). Interestingly, two different MIPS mRNA variants are present in tilapia gill epithelium.…”
Section: Mips/impa Mrna Versus Protein Regulationmentioning
confidence: 80%
“…As a result, a CSC whose DCLK1 promoter has been hypermethylated and cannot express DCLK1 anymore may still carry DCLK1 proteins that have been built before hypermethylation. Several different studies confirmed that the mRNA level of a gene does not necessarily predict its protein level [68][69][70][71]. To this reason, the evaluation of DCLK1 protein instead of DCLK1 mRNA may result in more valuable information.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reactions were observed with LPS-activated cells treated with CGRP for 48 h of incubation. These disparities between RNA and protein levels can be explained by a lack of correlation between gene expression and protein production and secretion [70,71,72]. Indeed, it has been detected that the expression and secretion profiles for cytokines in activated macrophages overlap but are temporally regulated [73].…”
Section: Discussionmentioning
confidence: 99%